2016
DOI: 10.1007/s11999-016-4811-6
|View full text |Cite|
|
Sign up to set email alerts
|

Low Frequency of Early Complications With Dual-mobility Acetabular Cups in Cementless Primary THA

Abstract: Background Dislocation complicates 1% to 5% of primary total hip arthroplasties (THAs). As a result, some surgeons consider dual-mobility articulations, which are usually used in the revision setting to decrease the likelihood of dislocation, as an option for primary THA. However, few studies have evaluated their use in this setting. Questions/purposes (1) What is the cup survivorship when the dual-mobility articulation is used in the setting of primary THA? (2) What are the clinical outcomes with this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
7
22
0
3
Order By: Relevance
“…Chughtai et al. (2016) reported 453 primary DMC THA with 2 septic revisions after 2 years. Differences in patient characteristics and particularly comorbidities are probably the explanation for our high amount (0.3%) of revisions due to suspected infection (Radtke et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chughtai et al. (2016) reported 453 primary DMC THA with 2 septic revisions after 2 years. Differences in patient characteristics and particularly comorbidities are probably the explanation for our high amount (0.3%) of revisions due to suspected infection (Radtke et al.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, the results of this study are similar to that of a recent multicenter study that evaluated 453 primary THA patients who received the modular dual mobility articulation where aseptic and all-cause survivorship was found to be 99.6% (95% CI, 99.1-99.9%) and 99.2% (95% CI, 98.5-99.9%), respectively. 13 Similar to this 7-year minimum follow-up study, Farizon et al 14 reported 0.7% dislocation rate on 135 cementless dual mobility hips at a minimum follow-up of 10 years with 95% implant survivorship at 12 years following THA. In an analysis of 150 dual mobility THAs, Bauchu et al 15 also demonstrated a cup survivorship of 97% and a dislocation rate of 0% after a mean follow-up period of 6 years.…”
Section: Discussionmentioning
confidence: 55%
“…With a cup survivorship of 100% in the younger group and 99.7% in patients above 70 years of age, Epinette et al demonstrated that good implant fixation with no evidence of migration, osteolysis, or intraprosthetic dislocation can be achieved with dual mobility cup THA. 16 Similarly, Chughtai et al 13 did not report any incidences of progressive radiolucencies or positional changes of components at the latest follow-up. And, in respect to clinical outcomes, Chughtai et al 13 reported a mean HHS score of 94 AE 6 points after a mean follow-up of 3 AE 1 years in 453 patients who underwent primary THA with a modular dual mobility cup construct.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chughtai et al. [9] also found a dislocation rate of 0% for the MDM implant at 3-year follow-up and a survivorship of 99.3%, which is consistent without 98%. All 3 studies had a 0% revision rate due to mechanical revisions, which is consistent with our revision rates of 0% in the ADM group and 0% in the MDM group due to acetabular-specific revisions.…”
Section: Discussionmentioning
confidence: 67%